2008
DOI: 10.1007/s12272-001-1281-7
|View full text |Cite
|
Sign up to set email alerts
|

Structure activity relationship studies of anti-inflammatory TMMC derivatives: 4-Dimethylamino group on the B ring responsible for lowering the potency

Abstract: We previously synthesized 2',4',6'-tris(methoxymethoxy)chalcone (TMMC) derivatives with various substituents on the A ring that showed potent anti-inflammatory effects by inhibiting NO production in RAW 264.7 cells. The 2'-hydroxy group on the A ring could elevate the electrophilicity of Michael addition of GSH and electron donating groups on the A ring could stabilize the GSH adduct by decreasing the acidity of the alpha-hydrogen. Using this interpretation, we tested various substituents on the B ring and est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…At 300 min the absorption of 2 was reduced to 83 %, whereas that of 3 was 70 % of the respective initial values. This observation is in agreement with the expected stability of the adducts which is affected by the different degree of electron donation of the two substituents [8].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…At 300 min the absorption of 2 was reduced to 83 %, whereas that of 3 was 70 % of the respective initial values. This observation is in agreement with the expected stability of the adducts which is affected by the different degree of electron donation of the two substituents [8].…”
Section: Resultssupporting
confidence: 91%
“…Such a reaction can alter the intracellular redox status (redox signaling), which can modulate events such as DNA synthesis, enzyme activation, selective gene expression, and regulation of the cell cycle [6]. Several biological effects (e.g., NQO1 inducer [7], anti-inflammatory [8], and GST P1-1 inhibitory [9] effects) of chalcones have been associated with their Michael-type reactivity towards reduced glutathione (GSH). It was suggested that the lower GSHdepletion potential of chalcones with strong electron donor substituents (e.g., dimethylamino) on the B ring could be the consequence of the lower Michael-type reactivity of the derivatives towards GSH [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a reaction can alter intracellular redox status (redox signaling), which can modulate events such as DNA synthesis, enzyme activation, selective gene expression, and regulation of the cell cycle . Several biological effects (e.g., NQO1 inducer, anti‐inflammatory, GST P1‐1 inhibitory) of chalcones have been associated with their Michael‐type reactivity toward reduced glutathione (GSH). It was suggested that the lower GSH depletion potential of chalcones with strong electron donor substituents (e.g., dimethylamino) on the B ring could be the consequence of the lower Michael‐type reactivity of the derivatives toward GSH .…”
Section: Introductionmentioning
confidence: 99%
“…Despite their apparent lack of specificity, chalcones were described to target distinct regulatory proteins that modulate downstream signaling pathways. Specific structural requirements play an essential role and can be correlated with observed bioactivity [63][64][65][66][67]. Identification and characterization of natural chalcones as nutraceuticals or as novel therapeutic agents is a promising approach to fight inflammation and cancer [31,32,39].…”
Section: Chalconesmentioning
confidence: 99%